Implementasi Pendekatan Komunikatif (Communication Approach) Dalam Meningkatkan Keterampilan Berbahasa Arab - Zaid, Abdul Hafidz bin; Widyanti, Lina Nur; Ismail, Moh; Jannah, Dias Ayu Miftakhul (STIQ Amuntai, 2024)
AbstractThe approach can be interpreted in English is (approach), which is a statement of establishment, philosophy and belief. Communicative means being able to convey messages well. The communicative approach is a language learning approach that emphasizes the mastery of language skills than language structure Language is a means of communication with each other, so that if someone does communication interaction, of course, must understand each other the object being discussed so that the goals to be achieved will be more directed towards their goals. However, if the interaction is not communicative because it does not understand what is being discussed because it does not understand the language used, causing the expected goals will not be achieved. Language is considered as a skill, not science, so language skills should be able to include four things, namely listening, speaking, reading, and writing. And one of the characteristics of these skills is to be done by continuous training. If one of the methods used previously is a direct method (direct method), then this method is updated so that it becomes an audiolingual method. The writing of this article aims to describe the application of a communicative approach through various learning methods in Arabic learning to increase language disappearances. The method used is the library research method originating from various library sources. The results of this writing indicate that methods that emphasize more to listening and speaking skills. Speaking skills are one type of language ability to be achieved in teaching Arabic. And in essence is a meter of reproducing the flow of the sound system of articulation to convey the will, the needs of feelings, and desires to others. Exercise in Arabic language so that students are able to communicate well and correctly with others. Starting the practice of speaking is based on the ability to listen, the ability to mastery vocabulary and courage to reveal what is in his mind.